Impending barbarism - Rudy, Andrew Jackson (My University, 1891)
Introduction: The whole life of a nation is not covered by its politics and economics. The culture of a nation consists of more than free political institutions and material prosperity. The morality of a community, its observance of law and order, its freedom from a degrading pauperism, its ideals of social life, are, in fact, the very indices of its civilization. In the attainment of these, it is with profound interest that one realizes man’s struggle for more perfect liberty. In fact the history of mean is that of one continuous and unremitted struggle for freedom. The struggle of Christianity within the prison walls of priestcraft and superstition, the rise and decay of the Roman Empire, the energetic and finding influence of the Feudal System, the inquiring spirit wrought by The Lutherian Reformation, as well as the inevitable results of modern some, wretched race, demands the earnest attention of every true, honest, humanity-loving citizens.
Citation: Rudy, Andrew Jackson. Impending barbarism. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Politics; Economics; Barbarism; Theses; Manuscripts (documents)